The effectiveness and safety of one-stage iStent-based micro-invasive glaucoma surgery—A retrospective study - Hajduga-Szewczyk, Marta; Smedowski, Adrian; Filipecka, Iwona; Mrukwa-Kominek, Ewa (Frontiers in Medicine, 2023)
Purpose Micro-invasive glaucoma surgery involves a group of treatment methods associated with a low rate of side effects and good effectiveness outcomes. One of the most frequently performed procedures belonging to this group is iStent microstent implantation. The aim of this study was to perform a retrospective evaluation of the safety and efficacy of a combined procedure involving cataract phacoemulsification and single iStent microstent implantation, performed simultaneously. Materials and methods The complete medical records of 62 patients (91 eyes) were analyzed retrospectively, including the best corrected visual acuity, intraocular pressure, the mean defect of visual fields, and the number of active substances used in eye drops. The follow-up times were 1, 3, 6, 9, and 12 months after the surgical procedure. Results A significant improvement in the best corrected visual acuity and a reduction of the intraocular pressure were achieved after the surgery. On average, after 12 months, the best corrected visual acuity improved from 0.70 (0.25) to 0.91 (0.18; p = 0.001), the intraocular pressure reduced from 17.76 (3.95) to 14.91 (3.04; p = 0.0001), and the number of active substances used in eye drops reduced from 2.07 (1.08) to 0.70 (0.06; p = 0001). In addition, we found that patients who initially showed higher intraocular pressure values did not benefit from surgery in the aspect of the number of active substances used in their eye drops. Intraoperative and postoperative adverse events were transient and ultimately did not affect the outcomes. Conclusion Simultaneous cataract phacoemulsification with single iStent implantation in patients with open-angle glaucoma is a safe and effective method for reducing intraocular pressure and the number of topical medications that must be used. Having initially higher intraocular pressure values may limit the beneficial effects of iStent implantation by subordinating patients from topical treatment; thus, single iStent implantation may not be the most favorable choice in uncontrolled glaucoma cases.